MUSLIM WOMEN AND POLITICS OF INDIA - Aadil Ahmad Shairgojri; Rashid Manzoor Bhat (RADJA PUBLIKA, 2023)
Politics is the progeny of political engagement, which is the mother. As it produces, nurtures, develops, rules, and shapes politics, the former is of utmost importance to both the country and the individual. Because of this, political engagement in every aspect of a nation's affairs defines its politics, and despite the fact that women make up close to half of the population, their political importance is far less than that of men. Women make up the bulk of the population. Women have always been viewed as second-class citizens in communities where men dominated, as is evident from history. The potential of women has been limited by forcing them to carry out domestic tasks within of four walls. Indian women were not allowed to leave their homes. Their freedoms and rights had been revoked. Enrolling them in school was prohibited. They had an idea of the perfect housewife. They have no access to opportunities in society, politics, the economy, or health. Women must be given more influence if civilisation is to advance. Muslims have a tremendous influence on Indian society. The largest minority in this nation is them. In 2011, the overall population of India was 13.4% Muslim, with the majority of them residing in Lakshadweep and Jammu & Kashmir. Emerging nations like India are currently concerned about the empowerment of women. It is thought that a number of factors, including the